Hidden participants and unheard voices? A systematic review of gender, age, and other influences on local and traditional knowledge research in the North - Maaya K. Hitomi; Philip A. Loring (Canadian Science Publishing, 2018)
Local, lay, and traditional ecological knowledge (LTK) is widely discussed in academic studies of climatic and environmental change. Here, we report on a systematic literature review that examines the role of such factors as gender, age, and scholarly networks in shaping LTK research. We focused on research in the circumpolar North, where LTK research has been ongoing for at least four decades. We explored how recruitment approaches and research methods can circumscribe local expertise and found that much of the literature fails to adequately report sampling and participant demographics. There is an apparent bias towards male knowledge-holders, usually hunters and Elders, over women and youth. Studies were largely led by male authors, and male authors outnumbered female authors 2:1. We also identified two potential "invisible colleges" in the literature-communities of practice linked by one or a few authors. We discuss our findings through the lens of "intersectionality", which captures how power differences at play within communities, whether around age or gender or some other social categorization, contribute to the creation of multiple kinds of knowledge. We conclude with a discussion of how we can improve this area of research by challenging assumptions and collaborating with a wider range of individuals.